Муҳаммадниёз Нишотийнинг «Ҳусн-у дил» достони ва кубравийлик таълимотидаги «ўн усул» ҳамда ранглар талқини (SCIENCE and SOCIETY, 2021)
Philosophical thoughts and moral views in Muhammadniyaz Nishoti’s epic "Husn-u Dil" of collection are interconnected with the ideas of N.Kubro’s creativity. The first similarity in their works is that there is an improvement in divine desire and divine beauty, the